"It is not only the guilty who suffer" : exploring gender, power and moral politics through the contagious diseases acts in the Cape Colony, c1868-1885 - Beukes, Danike Nanine (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2014.